Pathogenesis of pancreatic cancer (2008)
Pancreatic Adenocarcinoma is a lethal disease for which early detection has not improved survival rates. Studies in the last two decades have shown that pancreatic cancer is fundamentally a genetic disease caused by inherited germ lines and acquired somatic mutations in genes associated with cancer. Multiple alterations of genes that are important in the progression of pancreatic cancer have been identified. It is possible that better understanding of these alterations will facilitate identification of new biomarkers for early detection and may lead to novel drug targets. © 2008 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.